The Effect of Giving Rewards on Fifth-Grade Elementary Students’ Mathematics Learning Outcomes - Darinda Sofia Tanjung; Juliana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper determines the effect of giving rewards on the mathematics learning outcomes of fifth grade students at SDN 097388 Partuhan Simalungun in the academic year 2021/2022. The research population was 62 students of 5a and 5b classes at SD Negeri 097388 Partuhan. The research method used an experimental method with a quantitative research type. The instruments used to collect data were in the form of multiple-choice questions and questionnaires. The research results indicate that student learning outcomes using the reward method are in the very good category with an average of 83.2. The researcher used the normality test with the results of Lcount 0.200 > Ltable 0.05. Based on these calculations, it can be seen that the significant value is normally distributed. In the correlation test, the coefficient value is 0.710, which means that rcount > rtable 0.250. Therefore, the method of giving rewards to the mathematics learning outcomes of fifth-grade elementary students at 097388 Partuhan is influential. The results of the t-test are 7.803 > 1.679 so it is accepted. It indicates that there is a significant positive effect of giving rewards on the mathematics learning outcomes of fifth-grade students at SD Negeri 097388 Partuhan in the academic year 2021/2022.